Crops weather relationship in Tomato - AjithKumar B (Department of Agricultural Meteorology, College of Horticulture, 1999)
An experiment was conducted during 1997-98 at the College of Horticulture, vellanikkara to study to influence of date of sowing and levels of nitrogen on the growth and yield of tomato ((Lycopersicon esculentum Mill.) The experiment was laid out in split plot design with three replications. The treatment consisted of nine dates of planting starting from June 15th to February 15th in the main plot and two levels of nitrogen (125 kg N ha-1 and 75 kg N ha-1) in the subplot. Observations on morphological and yield attributes were recorded during the course of investigation. The daily values of various weather elements recorded at the Agromet observatory, college of Horticulture, Vellanikkara were collected to work out the crop weather relationship. February planted crop took less number of days for first flowering, 50 per cent flowering, and had the shortest crop duration. While June planting took maximum number of days for first and 50 per cent flowering. Where as maximum duration of the crop was recorded by planting in October. December planting was significantly superior to other treatments with regard to yield characters. The maximum number of fruits per plant was obtained for December planting followed by October and November planting. Application of 125 kg N ha-1 significantly improved the yield and yield characters as compared to that in 75 kg N ha-1. Higher dose of nitrogen favoured the earlier fruit set, maximum duration of the crop, increase in the number of fruits per plant and thus resulted in enhanced fruit yield. The crop weather relationship studies showed that the morning relative humidity and afternoon relative humidity during the 1st-2nd weeks after planting had a positive effect on the days to first flowering. The minimum temperature (7th-8th week) and morning relative humidity (6th-7th week) were negatively correlated with yield. Days to first flowering showed a negative correlationship with maximum temperature, minimum temperature, temperature range and hours of bright sunshine during the 1st-2nd weeks after planting. The maximum temperature of (31.60C-32.10C) and minimum temperature of 24.10C-24.30C) found to be optimum for early flowering. Wheras minimum temparature of (22.10C-23.30C) and relative humidity during morning hours (70-74%) during 6th and 8th week after planting are optimum for the increase yield. Under Vellanikkara condition, maximum temparature of 30.60C-33.70C, minimum temperature of 22.10C-24.30C, bright sunshine hours of 5.2-10.0, morning relative humidity of 70-86 per cent, afternoon relative humidity of 45-59 per cent is required for optimum crop growth. Based on the experimental data, minimum data set for the validation of tomato model of the IBSNAT has been generated. Result of the present experiment indicate that at Vellanikkara surrdounding tomato can be successfully raised if seedlings are planted in the middle of December. Weather during October and November are also congenial for getting higher yield. The higher dose of nitrogen (125 kg/ha) gave better yield than the recommended dose of nitrogen.